Improving Students' Critical Thinking Skills Using Multimedia in a Problem-Based Learning Model (PBL): a Narrative Review - Muda, Mhd. Abror Muzakkir; Siburian, Jodion; Musli, Musli (LPPM STKIP Kusuma Negara, 2025)
This study explores the impact of problem-based learning (PBL) models on students' critical thinking skills, particularly those integrated with multimedia. The research reviews existing literature on the use of multimedia in PBL and evaluates its effects on student learning outcomes. Using a quantitative approach focusing on quasi-experimental designs, the study analyzes findings from multiple studies demonstrating multimedia's positive influence of multimedia, such as videos, animations, and e-books, on critical thinking. The results show that while multimedia significantly enhances student engagement and problem-solving abilities, its effectiveness is also influenced by factors such as student motivation and teacher expertise in integrating technology. However, the adoption of multimedia in PBL remains limited across educational contexts, and long-term impacts remain underexplored. The study highlights the need for further research on the long-term effects of multimedia-supported PBL and emphasizes the importance of teacher training in utilizing multimedia tools effectively. The findings suggest that expanding multimedia use in PBL could improve critical thinking skills and learning outcomes, with potential benefits for educational practices and policy development.